Values and ethics for care practice - Cuthbert, Sue; Quallington, Jan (Lantern, 2017)
This book introduce readers to values and ethics and their importance in patient-centred care. Readers are encouraged to reflect on how values and ethics are articulated in the latest Codes of Practice and howthey can apply these concepts to become compassionate care professionals